1998
DOI: 10.1021/jo980999x
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Diphenyl(phenylethynyl)selenonium Salts with Active Methylene Compounds and Amides:  First Isolation of Oxyselenuranes [10-Se-4(C3O)] as a Reaction Intermediate

Abstract: The reaction of the diphenyl(phenylethynyl)selenonium triflate 1a with active methylene compounds 5 and t-BuOK in THF gave furan derivatives 6. The [10-Se-4(C3O)] selenuranes 8a and 8b could be isolated from the reactions with benzoylacetonitrile 5f and with 1,3-indandione 5g, respectively, as reaction intermediates. The structures of the selenuranes 8 were elucidated by X-ray crystallography and (77)Se high-resolution solid-state NMR spectroscopy. The selenuranes 8 underwent ligand coupling on standing at roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…Collins, Ratcliffe and Ripmeester [103] characterized the selenium chemical shift tensor of trimethylselenonium iodide as part of their investigation of numerous selenium containing compounds. Diphenyl(phenylethynyl)selenonium triflate, [PhC"CSePh 2 ][OTf], was prepared from the reaction of diphenylselenoxide, Ph 2 SeO, and phenylethynyl trimethylsilane, PhC"CSiMe 3 , and the observed value of d iso , 468 ppm, is consistent with those of other hypervalent organoselenium compounds found in Table 15 [300]. Dicationic 1,5-diselenacyclooctane trifluoromethane sulfonate (structure shown in Fig.…”
Section: Miscellaneous Organoselenium Systemssupporting
confidence: 64%
See 2 more Smart Citations
“…Collins, Ratcliffe and Ripmeester [103] characterized the selenium chemical shift tensor of trimethylselenonium iodide as part of their investigation of numerous selenium containing compounds. Diphenyl(phenylethynyl)selenonium triflate, [PhC"CSePh 2 ][OTf], was prepared from the reaction of diphenylselenoxide, Ph 2 SeO, and phenylethynyl trimethylsilane, PhC"CSiMe 3 , and the observed value of d iso , 468 ppm, is consistent with those of other hypervalent organoselenium compounds found in Table 15 [300]. Dicationic 1,5-diselenacyclooctane trifluoromethane sulfonate (structure shown in Fig.…”
Section: Miscellaneous Organoselenium Systemssupporting
confidence: 64%
“…The isotropic selenium chemical shifts, 454 and 451 ppm, for the compounds obtained, Fig. 16b and c, are similar to that of the reactant [PhC"CSePh 2 ][OTf], 468 ppm [300]. Analysis of the solid-state 77 Se NMR spectrum of diphenylselenium dichloride, Fig.…”
Section: Miscellaneous Organoselenium Systemsmentioning
confidence: 70%
See 1 more Smart Citation
“…It is known that trimethyloxonium tetrafluoroborate can react with the selenides to generate the corresponding selenonium salts. [15] These reactions were employed to effect the synthesis of several heterocyclic compounds by ring closure reactions. [16] We observed that using the trimethyloxonium tetrafluoroborate, the organoselenium group can also be substituted by a hydroxyl group.…”
Section: Entries 1-3)mentioning
confidence: 99%
“…[8] In particular, the tandem Michael addition-cyclization route between alkynylselenonium salts and active methylene carbanions afforded highly functionalized furan derivatives. [9] These interesting results prompted us to investigate a tandem reaction of an alkenylselenonium salt involving multiple carbon-carbon bond formation to afford carbanions derived from malonates reacted with the selenonium salt to afford 1,1-dicarbonylcyclopropane compounds in good yields. a useful compound.…”
Section: Introductionmentioning
confidence: 99%